Community-Acquired Pneumonia Caused by Avian Chlamydia abortus, the Netherlands - Jairo Gooskens; Einar H.R. van Essen; Margriet E.M. Kraakman; Patrick Wörz; Edou R. Heddema; Stefan A. Boers (Emerging Infectious Diseases)
We report avian Chlamydia abortus pneumonia in an immunocompetent elderly patient in the Netherlands after environmental exposure to wild aquatic birds, including seabirds. New molecular surveillance studies are needed in wild and captive birds, as well as increased awareness to establish occurrence, clinical manifestations, and geographic distribution of this rare zoonotic disease.